If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-8-2=-6x+12
We move all terms to the left:
5x-8-2-(-6x+12)=0
We add all the numbers together, and all the variables
5x-(-6x+12)-10=0
We get rid of parentheses
5x+6x-12-10=0
We add all the numbers together, and all the variables
11x-22=0
We move all terms containing x to the left, all other terms to the right
11x=22
x=22/11
x=2
| 5y-7=y+21 | | 0.25x+7=4(1x-2) | | 23/4=x/12 | | 4(2x-1)=9x+5 | | -6y+3(y-7)=-27 | | 70-x=190 | | 4x+10-7=4x-2x+17 | | 7+17X=12x-3 | | 12-4x=-2x+2 | | 3936=(p+32) | | -4k+3.6=7.8= | | m/26=2 | | 3936=(p+32 | | -4x+8(1)=-4 | | -8+d=7 | | 7x-2=2x-+8 | | 7x-23-2x=-58 | | 46+9a+5a=74 | | -0.5(12x-6)-4=35 | | 7x+3=3+5 | | 2.3-(-2.3)=n | | 101010101010x+10=101001010101010010111 | | 1(4)=-20x10 | | 7x+5+x=11 | | r/6=0 | | x+8232=283748 | | 3a−24= 9 | | x+12931=12931 | | 15(z+2)+1= | | 7x-21=18” | | 0.1=t^2-18.39t | | 364x+1923=1023912 |